CONSTRUCTION OF REALITY THE ATTACK OF CONSTITUTIONAL COURT (A Semiotics Analysis of Roland Barthes Model A Caricature Illustration in Inilah.com November, 16 2013) - Ari Cahyo Nugroho (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
Inilah.com website through a caricature illustrates how the Supreme Judge ran out of Constitutional Court which is being ravaged by the mass. Caricature entitled ‘Hukum Rimba di Mahkamah Konstitusi’ describes how the attitude of the Constitutional Court judges face the aggressive behavior a group of people. Although shape of a caricature, this image is a communication message that a reflection of the media attitude. In this article, the authors use Ronald Barthes model of semiotics, with connotation and denotation model of as the key analysis. In denotation exposure, this caricature depict women and men ran away from the collapse building. The woman in figure using verbal words that read ‘hukum di negeri ini sedang sakit, malah tambah diinjak-injak’. The other male figure, described was watching from a distance, He uttered the phrase verbal ‘sungguh memprihatinkan’. There is also a building reads ‘ Constitutional Court ‘ that almost collapsed stepped on the foot of a giant , black -legged and furry. Reads ’hukum rimba’. Sword and scales lying In front of the building ‘Constitutional Court’. While in connotation, raises critical toward the Constitutional Court is considered too scared to mass attitudes. Raising a soft and weak attitude. Caricature is reflect the current the Constitutional Court, due began to fade.Keywords: Construction of Reality; Semiotics